A computational framework for testing hypotheses of the minimal mechanical requirements for cell aggregation using early annual killifish embryogenesis as a model - Montenegro-Rojas, Ignacio; Yañez, Guillermo; Skog, Emily; Guerrero-Calvo, Oscar; Andaur-Lobos, Martin; Dolfi, Luca; Cellerino, Alessandro; Cerda, Mauricio; Concha, Miguel L.; Bertocchi, Cristina; Rojas, Nicolás O.; Ravasio, Andrea; et al. (Frontiers in Cell and Developmental Biology, 2023)
Deciphering the biological and physical requirements for the outset of multicellularity is limited to few experimental models. The early embryonic development of annual killifish represents an almost unique opportunity to investigate de novo cellular aggregation in a vertebrate model. As an adaptation to seasonal drought, annual killifish employs a unique developmental pattern in which embryogenesis occurs only after undifferentiated embryonic cells have completed epiboly and dispersed in low density on the egg surface. Therefore, the first stage of embryogenesis requires the congregation of embryonic cells at one pole of the egg to form a single aggregate that later gives rise to the embryo proper. This unique process presents an opportunity to dissect the self-organizing principles involved in early organization of embryonic stem cells. Indeed, the physical and biological processes required to form the aggregate of embryonic cells are currently unknown. Here, we developed an in silico, agent-based biophysical model to test how cell-specific and environmental properties could determine the aggregation dynamics of early Killifish embryogenesis. In a first approach (cell autonomous system), we considered how intrinsic biophysical properties of the cells such as motility, polarity, density, and the interplay between cell adhesion and contact inhibition of locomotion drive cell aggregation into self-organized clusters. Second, we included guidance to cell migration through a taxis mechanism to resemble the activity of an organizing center inbuilt in the embryo environment. Our numerical simulations showed that random migration combined with low cell-cell adhesion is sufficient to maintain cells in dispersion and that aggregation can indeed arise spontaneously under a limited set of conditions following characteristic power laws, but, without environmental guidance, the dynamics and resulting structures do not recapitulate in vivo observations. Thus, an environmental guidance cue seems to be required for correct execution of early aggregation in early killifish development. However, the nature of this cue (e.g., chemical or mechanical) can only be determined experimentally. Our model provides a predictive tool that could be used to better characterize the process and, importantly, to design informed experimental strategies.